2012
DOI: 10.13031/2013.42487
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Bean Heating Uniformity and Quality as Influenced by Radio Frequency Treatments for Postharvest Disinfestations

Abstract: Developing effective and economically viable treatments that replace chemical phytosanitary and quarantine practices is urgently needed for the coffee bean industry to maintain competitiveness in domestic and international markets. The objective of this study was to determine coffee bean heating uniformity and quality as influenced by radio frequency (RF) treatments for postharvest disinfestations. A pilot-scale, 27 MHz, 6 kW RF unit was used to study RF heating uniformity, develop a treatment protocol, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…As for horizontal temperature distribution, results were shown in Figure 4(b) and (c). Edge heating phenomenon was observed in each layer, the center temperature was the lowest Some studies which used cylindrical containers obtained similar results (Ozturk et al, 2018; Pan et al, 2012), and similar heating patterns were also reported for corn flour (Ozturk et al, 2019), coffee bean (Pan et al, 2012), potato starch (Zhu et al, 2017). This is due to that the edge areas absorb more electromagnetic energy (Tiwari et al, 2011), so edges was heated faster than center.…”
Section: Resultssupporting
confidence: 64%
“…As for horizontal temperature distribution, results were shown in Figure 4(b) and (c). Edge heating phenomenon was observed in each layer, the center temperature was the lowest Some studies which used cylindrical containers obtained similar results (Ozturk et al, 2018; Pan et al, 2012), and similar heating patterns were also reported for corn flour (Ozturk et al, 2019), coffee bean (Pan et al, 2012), potato starch (Zhu et al, 2017). This is due to that the edge areas absorb more electromagnetic energy (Tiwari et al, 2011), so edges was heated faster than center.…”
Section: Resultssupporting
confidence: 64%